Further optimization of the mGlu5 PAM clinical candidate VU0409551/JNJ-46778212: Progress and challenges towards a back-up compound. Issue 17 (1st September 2015) - Zhou, Ya; Malosh, Chrysa; Conde-Ceide, Susana; Martínez-Viturro, Carlos Manuel; Alcázar, Jesus; Lavreysen, Hilde; Mackie, Claire; Bridges, Thomas M.; Daniels, J. Scott; Niswender, Colleen M.; Jones, Carrie K.; Macdonald, Gregor J.; et al.
Graphical abstract